Fission-fusion group dynamics in reindeer reveal an increase of cohesiveness at the beginning of the peak rut - Body, Guillaume; Weladji, Robert B.; Holand, Øystein; Nieminen, Mauri (Springer, 2015)
Knowledge of the processes of group formation is important to understand the evolution of animal societies. Ungulates typically aggregate during the breeding season. According to the self-organization theory, proximal processes such as mating tactics should explain variation in average group size through their influences on group dynamics. Here, we tested whether variation of the fusion rate or fission rate led to an increase of average group size at the beginning of the peak rut. We followed the movement of marked animals within an enclosed herd of reindeer Rangifer tarandus during two breeding seasons (2009 and 2011). We used synchronized GPS collars that fixed the animals' position every hour (2009) and every 15 min (2011). Group dynamics occurred in three steps as follows: (1) a continuous aggregation of groups, (2) a continuous departure of single females from these groups, and (3) the aggregation of these solitary females to form new groups. We attributed the increase in average group size mainly to a decrease in the number of groups due to a decrease in the group and individual splitting propensities, rather than to an increase of their merging propensities. A decrease in the splitting propensity at the beginning of the peak rut may be due to males herding females, female mate choice, or female harassment avoidance. Further research on fission-fusion group dynamics should calculate merging and splitting propensities by controlling for variables such as group size, group density, or habitat characteristics.
Keywords: caribou; global positioning system; harem; mating; sexual selection; sociality